42%
------------------------------------------------------
Answer
899
Step-by-step explanation:
99
Answer:
a(n)= a(n-1) .10
Clearly see the equation
you can do it directly Apply logic
Every n th term is 10 times of previous n-1 th term
That is common ratio an/a(n-1)= 10
So, We have to find 4 th term
So, 4 th term is simply
1st term × (common ratio)^(4-1)
-11( 10)^3
-11000
Thanks
Answer:D ( if you add +4 to the (x + 3)^2)
Step-by-step explanation:
Parent function is f(x) = x^2
A translation 3 units left gives y = )x + 3)^2
- and 4 up gives y = (x + 3)^2 + 4 - vertex form.
Standard form :
y = x^2 + 6x + 9 + 4
= x^2 + 6x + 13.